Cognitive-Behavioral Therapy for the Feeling of Psychological Loneliness - baali, moustafa (Journal of Social Sciences and Humanities, 2016)
Today, humans live in an era of anxiety, fear, and a series of continuous, overlapping conflicts experienced in the pursuit of balance and stability, exerting every possible effort. When an individual is unable to fulfill their desires, they often opt for isolation, losing communication and the sense of belonging with others. This withdrawal serves as an indicator of the onset of a psychological problem known as the Feeling of Loneliness. This is a painful sensation resulting from a subjective experience of heightened sensitivity; the individual feels unwanted and detached from others. Such a feeling stems from the perceived absence of satisfying social relationships and is often accompanied by symptoms of psychological stress. Behaviorists explain the feeling of loneliness by linking it to a conflict between the processes leading to activity and those leading to inhibition. This occurs due to the individual’s inability to relinquish old conditioned responses learned during childhood following inappropriate environmental experiences. This leads to the formation of maladaptive habits that hinder an effective, successful life with others and prevent the learning of more appropriate behavioral patterns in social relationships. Behaviorism also focuses on the psychosomatic symptoms arising from the experience of loneliness. Accordingly, behaviorists propose clinical plans to treat this condition. Through this scientific article, we will explore several studies that have addressed behavioral therapy programs aimed at alleviating the intensity of the feeling of loneliness.